Remoção de cor, turbidez e DQO de vinhaça utilizando adsorventes - Nippes, Ramiro Picoli (2016)
The sugarcane sector is one of the most important sectors of the current Brazilian industry and, in the process to obtain their products, sugar and alcohol mill produce some waste that deserve attention, including the vinasse, which is the residue from the alcoholic distillation process. Currently its main destination is in the own sugarcane fields‟ fertirrigation, where the vinasse is dispersed directly into the soil. However, this technique has generated discussions and driven the development of new methods of treatment for this residue, including adsorption process. In this context the objective of this study was to evaluate the performance of adsorbents in the removal of color, turbidity and COD of pretreated vinasse with coagulation / flocculation. Three adsorbents were used: commercial organophilic clay (AO), commercial bone charcoal (CO) and activated carbon produced from sugarcane bagasse (CB) using the process of pyrolysis and activated with NaOH. The adsorbents were characterized from the textural analysis, XRD, SEM, EDX, FTIR and tested under batch operation process. Adsorption isotherms were obtained and the data were adjusted to Langmuir and Freundlich models. The adsorption kinetics was studied for the process and the related thermodynamic parameters were calculated. The results indicated that the experimental equilibrium data of all tested adsorbents were better adjusted to the Langmuir isotherm, , and the adsorption kinetics was satisfactorily represented by pseudo-first order model. The thermodynamic parameters for the process showed spontaneous (ΔG ° <0) for all absorbents, showed an exothermic character (°ΔH <0) to the CO and CB and endothermic (°ΔH> 0) to organophilic clay. The entropy increased for adsorption with activated carbon and charcoal bone (ΔS°>0) and decreased for the organophilic clay (ΔS°<0). In relation to the adsorbents efficiency, it can be concluded that they were effective in the removal of the color parameters, turbidity and COD of vinasse, whereas the best achieved percentage of removal were 95.32% for color, 99% for turbidity and 88 55% for COD. The greater adsorbed amount was higher for AO of 0,00038 kgO2/kg at 50°C.